Tindakan Hukum yang Dapat Ditempuh terhadap Apoteker atas Kelalaian dalam Peracikan Obat - Habibburrohman Ridho; M. Bakas Pratama,; Muhammad Kurniawan Syahputra,; Magfi Rafiqih; Leo Agus Satria (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
The 1945 Basic Law states that it is the responsibility of the State to establish a social security system for everyone, empower the weak and incapable communities in accordance with human dignity, and provide adequate health services and public facilities to guarantee the rights of every citizen. Legal protection for victims of pharmacist negligence: Pharmacists have the right to protect the victim's family and property if they die, and victims are entitled to personal protection. They must also participate in the process of determining the kind of protection and security support they need.